Optical Injection and Lasing Dynamics in Long-Wavelength VCSELs With Intracavity Patterning - Long, Christopher M.; Mickovic, Zlatko; Ellafi, Dalila; Dwir, Benjamin; Iakovlev, Vladimir; Sirbu, Alexei; Mereuta, Alexandru; Caliman, Andrei; Kapon, Eli (IEEE journal of selected topics in quantum electronics, 2015)
We present the static and optical injection response of wafer-fused long-wavelength VCSELs with and without intracavity patterning. It is found that the extra optical cavity patterning increases the gain anisotropy between orthogonal polarization modes, increasing the polarization stability, and influencing the dynamic response of the device. Dynamics features are summarized on maps in the injection power-master/slave detuning plane, and good agreement is obtained with the spin-flip model of VCSEL polarization modes.